Real options valuation for South African nuclear waste management using a fuzzy mathematical approach - Montsho, Obakeng Johannes (Rhodes University, Faculty of Science, Department of Mathematics, 2013)
The feasibility of capital projects in an uncertain world can be determined in several ways. One of these methods is real options valuation which arose from financial option valuation theory. On the other hand fuzzy set theory was developed as a mathematical framework to capture uncertainty in project management. The valuation of real options using fuzzy numbers represents an important refinement to determining capital projects' feasibility using the real options approach. The aim of this study is to determine whether the deferral of the decommissioning time (by a decade) of an electricity-generating nuclear plant in South Africa increases decommissioning costs. Using the fuzzy binomial approach, decommissioning costs increase when decommissioning is postponed by a decade whereas use of the fuzzy Black-Scholes approach yields the opposite result. A python code was developed to assist in the computation of fuzzy binomial trees required in our study and the results of the program are incorporated in this thesis.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Fuzzy mathematics; Real options (Finance); Fuzzy sets; Business mathematics; Radioactive waste disposal -- South Africa